Reproduction and monogamy in captive flock of greater flamingos (Phoenicopterus Roseus). Issue 3 (3rd July 2018) - Sandri, Camillo; Sammarini, Carolina; Regaiolli, Barbara; Spiezio, Caterina; Piccirillo, Alessandra
ABSTRACT: Due to the great number of greater flamingos in captivity and their long life span, studying their behavior and welfare might be useful to improve the husbandry and breeding of this species in zoos. This study aimed to investigate factors affecting the breeding activity of captive greater flamingos ( Phoenicopterus roseus ) from 2012 to 2016. To estimate reproductive success, the number of pairs, eggs laid, and hatchlings were recorded. In addition, information on age, egg-laying history of the partners, and pair composition was collected. An increase in the number of pairs, eggs, and hatchlings was reported over the years. For each breeding season, there were pairs who laid more than once, especially in 2014 and 2015. Approximately 50% of pairs were monogamous between consecutive years; however, the percentage dropped gradually when comparing nonconsecutive years. Senescence and previous experience seemed to affect the reproductive success of the study flamingos. In conclusion, different factors can influence the reproduction of greater flamingos in zoos. All these factors are related to nonhuman animal welfare and need to be considered in developing and improving management practices.